Mixed connective tissue disease - R. U. Shayakhmetova; L. P. Ananyeva (Современная ревматология)
Mixed connective tissue disease (MCTD), also known as Sharp's syndrome, is a rare systemic connective tissue disorder that characterized by a combination of some features of systemic lupus erythematosus, systemic sclerosis, rheumatoid arthritis, polymyositis with the presence of antibodies to soluble nuclear ribonucleoprotein (anti-U1-RNP) in high titers. The most common clinical manifestations of MCTD include Raynaud's phenomenon, hand edema, muscle weakness, arthralgia/arthritis, and esophageal hypotonia. The course of the disease is mostly benign; however, there are severe cases with damage to the lung, kidneys, cardiovascular system and central nervous system. Poor prognosis and the highest mortality rate are associated with pulmonary hypertension. The diagnosis of MCTD is difficult due to the absence of unified diagnostic criteria and lack of specific manifestations at the onset of the disease. Furthermore, there are no generally accepted guidelines for MCTD treatment.The paper considers the modern concepts of MCTD, its current diagnostic criteria, clinical and immunological features, and treatment.